Non-Legionella pneumophila serogroup 1 pneumonia: Diagnosis of a nosocomial legionellosis with the Biofire Pneumonia plus panel. (2022) - Courboules, Camille; Dournon, Nathalie; Lawrence, Christine; Noussair, Latifa; Descours, Ghislaine; Sivadon-Tardy, Valérie; Jarraud, Sophie; Herrmann, Jean-Louis; Gaillard, Jean-Louis; Espinasse, Florence; El Sayed, Faten; Roux, Anne-Laure
Abstract: We report a nosocomial case of Legionella pneumophila pneumonia caused by a serogroup 10 strain diagnosed with the Biofire® Pneumonia plus panel. Molecular investigations of the environment of the patient allowed us to identify the source of contamination.